Need for invasive cardiological assessment and intervention: a ten year review. Issue 2 (February 1992) - MacRae, C A; Marber, M S; Keywood, C; Joy, M
Abstract : The uptake of invasive cardiological investigation and cardiopulmonary bypass procedures by the North West Surrey Health District was audited over the years 1979-88. Growth was almost continuous throughout the ten year period. The need within the district each year for coronary angiography seemed to be between 111 and 171 and for surgical revascularisation of the myocardium between 63 and 96 procedures; the first figure is the mean of the second quinquennial period (1984-88) and the second figure the total for 1988. After correction for the standardised mortality ratio and catchment area, the national requirement should lie between 690 and 1070 coronary angiograms and 390 and 600 coronary artery bypass graft operations per million population each year. There is a further national requirement for 70 valvar heart operations and 30 miscellaneous procedures per million population each year. Owing to delays in the provision of services, 20 patients died of a cardiovascular cause while they were on the waiting list for investigation or surgery. In the United Kingdom the annual target to be achieved by 1990 was 300 coronary artery bypass procedures per million population.